Reading Textbook for Students with Dyslexia Based on Teachers’ Good Practices in Primary Schools - Asep Supena; Indina Tarjiah; Septiyani Endang Yunitasari (Universitas Pendidikan Ganesha, 2026)
Reading difficulties are a primary characteristic of children with dyslexia, marked by challenges in word recognition, letter–sound correspondence, and text comprehension despite having adequate intellectual abilities. These difficulties are often exacerbated by the use of instructional materials that do not align with their learning characteristics. This study aims to analyze the characteristics of effective instructional materials to support reading instruction for children with dyslexia. The study employed a qualitative approach with a phenomenological design involving two experienced teachers who have taught reading to children with specific learning difficulties. Data were collected through semi-structured interviews and analyzed using thematic analysis techniques. The findings identified four main characteristics of effective instructional materials: (1) dyslexia-friendly design with clear and simple visual presentation; (2) reinforcement of phonological skills and vocabulary through explicit activities; (3) the use of adaptive media and learning resources that accommodate diverse learning styles; and (4) the implementation of a multisensory approach in reading instruction. The study concludes that inclusive, structured, and multisensory-based instructional materials play a crucial role in improving access to and the quality of early literacy for children with dyslexia. The implications of this study highlight the need for teachers and instructional material developers to design adaptive and multisensory-based learning materials to enhance the effectiveness of reading instruction in inclusive educational settings.